2021
DOI: 10.1371/journal.pone.0253503
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in sensorimotor function after ACL reconstruction during active joint position sense testing. A systematic review

Abstract: Background The anterior cruciate ligament (ACL) rupture can lead to impaired knee function. Reconstruction decreases the mechanical instability but might not have an impact on sensorimotor alterations. Objective Evaluation of the sensorimotor function measured with the active joint position sense (JPS) test in anterior cruciate ligament (ACL) reconstructed patients compared to the contralateral side and a healthy control group. Methods The databases MEDLINE, CINAHL, EMBASE, PEDro, Cochrane Library and SPOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, we did not observe significant differences between the two groups of patients, which may be due to a slightly underpowered ACL-R group. The impairments in semitendinosus muscle function [ 4 , 57 59 ] and proprioception [ 60 ] reported after ACL-R may explain the observed differences compared to controls. However, the presumed preservation of proprioception after ACL-IB remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe significant differences between the two groups of patients, which may be due to a slightly underpowered ACL-R group. The impairments in semitendinosus muscle function [ 4 , 57 59 ] and proprioception [ 60 ] reported after ACL-R may explain the observed differences compared to controls. However, the presumed preservation of proprioception after ACL-IB remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The JPS test examines the ability to reproduce a prior presented angle by a body segment 5 . The assessment can be conducted under active or passive conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have revealed sensorimotor alterations after joint injury, e.g., anterior cruciate ligament (ACL) rupture and reconstruction 5 , 13 . It is assumed that these alterations are related to impaired muscle functionality and diminished activity level or balance abilities after ACL injury 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations